Flame-retardant bio-based benzoxazine resin Poly (PT-fa) as well as preparation method and application thereof
By combining the bio-based benzooxazine monomer PT-fa with high rigidity and flexible structure, solvent-free synthesis and thermal curing preparation are achieved, and the problem of insufficient thermal stability and flame retardant properties of the resin in the prior art is solved, and a bio-based benzooxazine resin Poly (PT-fa) with high thermal stability and high flame retardant properties is obtained.
Patent Information
- Application Number
- CN202411490055.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-03-04
AI Technical Summary
The prior art is difficult to synthesize high-performance, fully bio-based flame-retardant benzoxazine resins under solvent-free method, resulting in insufficient thermal stability and flame-retardant properties of the resin, which cannot meet the needs of electronic packaging, aerospace and other fields.
By combining catechol groups and benzoxazine bifunctional groups with high rigid structure, using an ethanol structure with flexible segments, a solvent-free method was achieved to prepare the bio-based benzoxazine monomer PT-fa, and a flame-retardant bio-based benzoxazine resin Poly (PT-fa) was prepared by thermal curing.
The solvent-free method of synthetic bio-based benzooxazine resin has high thermal stability and high flame retardant properties. The Tdi is 310-330℃, the HRC is 15-25J/g·K, and the THR is 2-4kJ/g, which meets the needs of high-performance resins.
Smart Images

Figure CN119552332A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional polymer materials, and in particular to a flame retardant bio-based benzoxazine resin Poly (PT-fa) and a preparation method and application thereof. Background Art
[0002] In addition to heat resistance, flame retardancy and dielectric properties, benzoxazine also has molecular designability. However, the common high-performance benzoxazine resins currently have the characteristics of high rigidity structure, that is, the melting points of their synthetic raw materials and monomers are very high. This property directly leads to the fact that such benzoxazine must be synthesized by solvent method. For example, the existing document 1 (Anapigenin-based bio-benzoxazine with three polymerizable functionalities: sustainable synthesis, thermal latent polymerization, and excellent thermal properties of its thermosets, Polymer Chemistry, 2020, 11, 5800-5809) uses apigenin and furfurylamine as the main raw materials to synthesize all-biomass benzoxazine monomers. The initial thermal decomposition temperature Tdi of the cured resin is 384°C, the heat release capacity HRC is 20.2J / g·K, and the total heat release THR is 9.4kJ / g. The molecules used in this technical method have a highly rigid structure, and the melting point of its monomer is as high as 174°C. This property determines that the monomer cannot be prepared by a solvent-free synthesis method - this technical solution adopts a solvent method for preparation, specifically using toluene as a reaction medium. Therefore, the problem with this technical solution is that toxic solvents are used as raw materials on the surface. In addition to causing environmental pollution problems under high-temperature reaction conditions, toxic solvents also exist in residual materials, affecting the scope of subsequent applications. Therefore, it can be confirmed that the fundamental problem of this type of technical solution is that due to the basic properties of its monomers, it is impossible to use a solvent-free method for preparation, and thus cannot meet the requirements of green environmental protection.
[0003] At present, the common solution to achieve the solvent-free synthesis of bio-based benzoxazines is to introduce a large number of flexible structures into the molecules to achieve the purpose of lowering the melting point of raw materials and products. This solution directly leads to the technical problems of poor thermal stability and poor flame retardancy of the obtained cured resin.
[0004] In order to further confirm the existing technical solutions for preparing all-bio-based flame-retardant benzoxazine resins based on solvent-free method, the SCI database was searched and queried. The query results show that there are only 4 relevant academic papers, which are:
[0005] Existing literature 2 (Making benzoxazines greener: Design, synthesis, and polymerization of a biobased benzoxazine fulfilling two principles of greenchemistry, ACS Sustainable Chemistry Engineering, 2018, 6, 13096-13106);
[0006] Existing literature 3 (Biobased high-performance tri-furan functional bis-benzoxazine resin derived from renewable guaiacol, furfural and furfurylamine, European Polymer Journal, 2020, 131, 109706-109713);
[0007] Existing literature 4 (Development and characterization of fully bio-basedpolybenzoxazine-silica hybrid composites for low-k and flame-retardant applications, Polymers Advanced technologies, 2019, 30, 1856-1864);
[0008] Existing document 5 (High-Tg bio-based polybenzoxazine derived from renewable anethole and furfurylamine, European Polymer Journal, 2023, 199, 112466-112473).
[0009] The above four existing documents record and disclose a total of 9 fully bio-based flame-retardant benzoxazine monomers synthesized by a solvent-free method.
[0010] Among them, the existing document 2 uses biomass sesamol and furfurylamine as raw materials and adopts a solvent-free method to synthesize an all-biomass benzoxazine monomer. The T diThe temperature is 317°C and the HRC is 201 J / g·K. Although this technical solution uses low-melting-point monophenol and monoamine as raw materials and successfully achieves solvent-free synthesis, the resulting resin has poor heat resistance and flame retardancy because the raw materials are monofunctional benzoxazine.
[0011] In addition, in the existing document 3, biomass guaiacol and furfurylamine are used as raw materials, and a solvent-free method is used to synthesize a bifunctional benzoxazine based on a monofunctional resin. The HRC of the resin is 70.6 kJ / g and 30.4 kJ / g, and the THR is 6.5 kJ / g and 5.8 kJ / g. Although this technical solution improves the flame retardant properties of the resin by using bifunctional benzoxazine as a raw material, this technical solution still has two technical problems:
[0012] 1. The synthesis steps are complicated;
[0013] 2. Due to the presence of methoxy groups in the structure, the flame retardant properties of the resin are significantly weakened.
[0014] In short, the nine resins provided by the prior art cannot achieve an HRC lower than 30 J / g·K or a THR lower than 5 kJ / g. Therefore, they cannot meet the flame retardant performance requirements of resins in the fields of electronic packaging, aerospace, and military.
[0015] In summary, the current prior art cannot achieve both solvent-free synthesis and high performance of the resin. The reason is that the rigid structure hinders the implementation of the solvent-free synthesis method, and the flexible structure affects the performance of the resin. Summary of the invention
[0016] In view of the problems existing in the prior art, the present invention provides a flame retardant bio-based benzoxazine resin Poly (PT-fa) and a preparation method and application thereof.
[0017] The basic principle of the present invention is to achieve solvent-free preparation based on biomass raw materials by forming a combination of rigid structure and flexible structure. Specifically, the high thermal stability and high flame retardant performance of the resin are achieved by utilizing the catechol group and benzoxazine bifunctional group with a high rigidity structure; the melting point of the benzoxazine monomer is greatly reduced by utilizing the ethanol-based structure with a flexible chain segment, so that the monomer can be synthesized by a solvent-free method and the resulting resin has high processability. The specific preparation method involved is, first, heating hydroxytyrosol, furfurylamine and polyformaldehyde to obtain a bio-based benzoxazine monomer; then, the obtained bio-based benzoxazine monomer is cured to obtain a flame-retardant bio-based benzoxazine resin.
[0018] In order to achieve the above object, the technical solution adopted by the present invention is:
[0019] A flame retardant bio-based benzoxazine resin Poly (PT-fa), wherein the cured resin Poly (PT-fa) is prepared by thermally curing the bio-based benzoxazine monomer PT-fa, and the obtained resin has high thermal stability and high flame retardancy;
[0020] The PT-fa is prepared by a solvent-free synthesis method using hydroxytyrosol, furfurylamine and paraformaldehyde as raw materials. The obtained monomer has high purity and a yield of 80-90%.
[0021] The temperature T at which the Poly(PT-fa) loses 5% of its weight under nitrogen atmosphere di The residual carbon rate Y at 310-330℃ and 800℃ c It is 60-70%; the heat release capacity HRC is 15-25J / g·K, and the total heat release THR is 2-4kJ / g.
[0022] A method for preparing a flame retardant bio-based benzoxazine resin Poly (PT-fa), comprising the following steps:
[0023] Step 1, preparation of bio-based benzoxazine monomer PT-fa, hydroxytyrosol, furfural amine and paraformaldehyde satisfying a certain amount of substance ratio, hydroxytyrosol, furfural amine and paraformaldehyde are mixed, and a Mannich condensation reaction is carried out under certain conditions by a solvent-free method. After the reaction is completed, the bio-based benzoxazine monomer is obtained after recrystallization and drying, which is referred to as PT-fa;
[0024] In the step 1, the molar ratio of hydroxytyrosol, furfurylamine and paraformaldehyde is 1:2:4;
[0025] In the step 1, the conditions for the Mannich condensation reaction are: in an oil bath and under stirring conditions, the reaction temperature is 110° C. and the reaction time is 6 h;
[0026] In the step 1, the recrystallization operation is carried out in ethanol;
[0027] Step 2, curing of the heat-resistant bio-based benzoxazine resin, first, completely melting the PT-fa obtained in step 1 under certain conditions, then placing the molten PT-fa in a mold, and finally curing the PT-fa to obtain the heat-resistant bio-based benzoxazine resin, referred to as Poly(PT-fa);
[0028] In step 2, the conditions for complete melting of PT-fa are as follows: the heating temperature is 115-140° C. and the heating time is 5-30 min;
[0029] In step 2, the curing conditions are divided into 4 stages:
[0030] Stage 1: curing temperature is 180°C and curing time is 1h;
[0031] Stage 2: curing temperature is 200°C and curing time is 1h;
[0032] Stage 3: curing temperature is 220°C and curing time is 1h;
[0033] Stage 4 is a curing temperature of 240°C and a curing time of 2 hours.
[0034] The technical effect of the present invention can be known through the following tests:
[0035] The HRMS test results show that the mass-to-charge ratio is 397.1740, which is consistent with [C 22 H 25 N2O5] + The difference from the theoretical value of mass-to-charge ratio of 397.1764 is negligible. The test results show that PT-fa was successfully synthesized.
[0036] The FTIR test results show that PT-fa contains characteristic peaks of CN, COC, oxazine ring, ethylene in ethanol group and hydroxyl peak. The test results show that PT-fa was successfully synthesized.
[0037] go through 1 The H NMR test results show that PT-fa contains the characteristic hydrogen spectrum of furan ring, benzene ring, methylene on oxazine ring, and methylene and ethylene connecting furan ring, without other obvious impurity peaks. The test results show that PT-fa was successfully synthesized and has high purity.
[0038] go through 13 The C NMR test results show that PT-fa contains the characteristic carbon spectra of the methylene on the oxazine ring, the methylene connected to the furan ring, and the ethylene. The test results show that PT-fa was successfully synthesized.
[0039] The DSC test results show that the melting point of PT-fa is 113.8°C and the peak curing temperature is 224.9°C. The test results show that PT-fa has a low melting point and curing temperature, which directly leads to the solvent-free synthesis method of PT-fa, that is, PT-fa has excellent processing performance.
[0040] The FTIR test results show that the characteristic peaks of CN, COC and oxazine rings disappear. Comparing the test results with the FTIR spectrum of PT-fa, it can be seen that PT-fa undergoes a ring-opening cross-linking reaction to form a cured resin Poly (PT-fa).
[0041] The TGA test results show that the temperature T at which Poly(PT-fa) loses 5% of its weight under nitrogen atmosphere isdi The residual carbon rate Y at 310-330℃ and 800℃ c The test results show that Poly(PT-fa) has good thermal stability.
[0042] The MCC test results show that the heat release capacity HRC of Poly(PT-fa) is 15-25J / g·K, and the total heat release THR is 2-4kJ / g. The test results show that the HRC and THR of Poly(PT-fa) are lower than the HRC and THR values of the curing resin of all-bio-based benzoxazine synthesized by the existing solvent-free method, which indicates that Poly(PT-fa) has excellent flame retardant properties.
[0043] Compared with the prior art, the present invention has the following advantages:
[0044] 1. The present invention uses biomass hydroxytyrosol and furfurylamine as main raw materials, and can synthesize and purify bio-based benzoxazine monomer (PT-fa) by solvent-free method or in green solvent ethanol;
[0045] 2. The PT-fa obtained in the present invention has excellent processability, which is specifically reflected in that the melting point (T m ) is 113.8℃;
[0046] 3. The Tdi of the benzoxazine resin (poly(PT-fa)) prepared by the present invention is 326°C, and the carbon residue rate (Y c ) is 65.8%, HRC is 21.3 J / g·K, and THR is 2.9 kJ / g. The HRC and THR values are lower than those of all the solvent-free synthesized all-bio-based benzoxazine curing resins; poly(PT-fa) not only has good thermal stability, but also has outstanding flame retardant properties.
[0047] 4. The PT-fa synthesized in the present invention can be blended with the commercial benzoxazine monomer (BA-a) in a molten state or in the green solvent ethanol to further prepare a copolymer resin; when the PT-fa content is 20%, the Tg, Tdi and Yc of the copolymer resin are increased by 55.8°C, 7°C and 5%, respectively, and the HRC and THR are reduced by 14.3% and 18%, respectively, compared with the commercial resin; when the PT-fa content is 40%, the Tg, Tdi and Yc of the copolymer resin are increased by 55.8°C, 7°C and 5%, respectively, compared with the commercial resin; g , T di and Y c The temperatures increased by 78.6℃, 10℃ and 11.8% respectively; HRC and THR decreased by 33% and 35% respectively; the addition of PT-fa significantly improved the heat resistance and flame retardancy of commercial resins. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a high resolution mass spectrum HRMS graph of the bio-based benzoxazine monomer in Example 1 of the present invention;
[0049] Figure 2 is the Fourier transform infrared FTIR spectrum of the bio-based benzoxazine monomer in Example 1 of the present invention;
[0050] Figure 3 is the nuclear magnetic resonance hydrogen of the bio-based benzoxazine monomer in Example 1 of the present invention 1 H NMR spectrum;
[0051] Figure 4 is the nuclear magnetic resonance carbon of the bio-based benzoxazine monomer in Example 1 of the present invention 13 C NMR spectrum;
[0052] Figure 5 is the synthesis reaction formula and chemical structure formula of the bio-based benzoxazine monomer in Example 1 of the present invention;
[0053] Figure 6 is a differential scanning calorimetry DSC graph of the bio-based benzoxazine monomer in Example 1 of the present invention;
[0054] Figure 7 This is the FTIR spectrum of the bio-based benzoxazine resin in Example 1 of the present invention.
[0055] Figure 8 is a thermogravimetric TGA graph of the bio-based benzoxazine resin in Example 1 of the present invention;
[0056] Fig. 9 is a heat release rate HRR-temperature curve in a micro combustion calorimetry MCC test of the bio-based benzoxazine resin in Example 1 of the present invention;
[0057] Fig.10 is the thermogravimetric TGA graph of Poly(BA-a) in Comparative Example 1 of the present invention;
[0058] Fig.11 is the HRR-temperature curve of Poly(BA-a) in Comparative Example 1 of the present invention;
[0059] Fig.12 is the nuclear magnetic resonance hydrogen of the bio-based benzoxazine monomer in comparative example 2 of the present invention. 1 H NMR spectrum;
[0060] Fig.13 is the nuclear magnetic resonance hydrogen of the bio-based benzoxazine monomer in comparative example 3 of the present invention. 1 H NMR spectrum;
[0061] Fig.14It is the HRR-temperature curve of the bio-based benzoxazine monomer in Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0062] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but is not intended to limit the present invention.
[0063] Example 1
[0064] A method for preparing a flame retardant bio-based benzoxazine resin comprises the following steps:
[0065] Step 1, preparation of bio-based benzoxazine monomer PT-fa, with the molar ratio of hydroxytyrosol, furfurylamine and paraformaldehyde being 1:2:4, 10.962g hydroxytyrosol, 13.809g furfurylamine and 8.542g paraformaldehyde are mixed, that is, the total mass of the raw materials is 33.313g, and a Mannich condensation reaction is carried out under the conditions of a solvent-free method, an oil bath and stirring, a reaction temperature of 110°C, and a reaction time of 6h. After the reaction is completed, after recrystallization and drying, a bio-based benzoxazine monomer, referred to as PT-fa, can be obtained;
[0066] The recrystallization operation is carried out in ethanol.
[0067] In order to prove the successful synthesis of PT-fa, HRMS test was performed. The test results are shown in Figure 1 As shown, the measured value of the mass-to-charge ratio is 397.1740, which is consistent with [C 22 H 25 N2O5] + The difference from the theoretical value of mass-to-charge ratio of 397.1764 is negligible. The test results show that PT-fa was successfully synthesized.
[0068] In order to further prove the successful synthesis of PT-fa and confirm the composition of PT-fa, FTIR test was performed. The test results are as follows Figure 2 As shown, PT-fa contains characteristic peaks of CN, COC, oxazine ring, ethylene in ethanol group and hydroxyl peak. The test results show that PT-fa was successfully synthesized.
[0069] In order to further prove the successful synthesis and purity of PT-fa, 1 H NMR testing and 13 C NMR test.
[0070] 1 The results of H NMR tests are as follows Figure 3As shown, PT-fa contains the characteristic hydrogen spectrum of furan ring, benzene ring, methylene on oxazine ring, methylene and ethylene connecting furan ring, and no other obvious impurity peaks. The test results show that PT-fa was successfully synthesized and has high purity.
[0071] 13 C NMR test results are as follows Figure 4 As shown, PT-fa contains the characteristic carbon spectrum of the methylene group on the oxazine ring, the methylene group connected to the furan ring, and the ethylene group. The test results show that PT-fa was successfully synthesized.
[0072] In order to prove the yield of PT-fa, the mass of PT-fa obtained in step 1 was weighed. The mass of PT-fa was 28.019 g, and it was calculated that the yield of PT-fa was 84.1%.
[0073] The bio-based benzoxazine monomer PT-fa was synthesized for the first time and there is no existing synthesis reaction formula. According to the above HRMS test, FTIR test and NMR test, it can be confirmed that the synthesis reaction formula of PT-fa is as follows: Figure 5 As shown, PT-fa is synthesized by a solvent-free method using hydroxytyrosol, furfurylamine and paraformaldehyde as reactants and a Mannich condensation reaction under heating conditions.
[0074] Since PT-fa was synthesized for the first time and there is no existing thermal performance data, DSC test was performed to prove the thermal performance of PT-fa, that is, its processing performance. Figure 6 As shown, the melting point of PT-fa is 113.8°C and the peak curing temperature is 224.9°C. The test results show that PT-fa has a lower melting point and curing temperature, which directly leads to the solvent-free synthesis method of PT-fa, that is, PT-fa has excellent processing properties.
[0075] Step 2, curing of heat-resistant bio-based benzoxazine resin, first, the PT-fa obtained in step 1 is completely melted at a heating temperature of 130° C. for 10 minutes, then the molten PT-fa is placed in a mold, and finally, the PT-fa is cured to obtain a heat-resistant bio-based benzoxazine resin, referred to as Poly(PT-fa).
[0076] The curing is divided into 4 stages:
[0077] Stage 1: curing temperature is 180°C and curing time is 1h;
[0078] Stage 2: curing temperature is 200°C and curing time is 1h;
[0079] Stage 3: curing temperature is 220°C and curing time is 1h;
[0080] Stage 4 is a curing temperature of 240°C and a curing time of 2 hours.
[0081] In order to prove the successful preparation of Poly(PT-fa), FTIR test was performed. The test results are as follows Figure 7 As shown, the characteristic peaks of CN, COC, and oxazine rings disappeared. Comparing the test results with those in step 1, it can be seen that PT-fa undergoes a ring-opening cross-linking reaction to form a cured resin Poly(PT-fa).
[0082] In order to prove the thermal stability of Poly(PT-fa), TGA test was performed. The test results are as follows Figure 8 As shown, the temperature T at which Poly(PT-fa) loses 5% of its weight under nitrogen atmosphere di The residual carbon rate Y at 326℃ and 800℃ c The test results show that Poly(PT-fa) has good thermal stability.
[0083] In order to prove that Poly(PT-fa) has flame retardant properties, a micro combustion calorimetry MCC test was performed. The test results are as follows Fig. 9 As shown, the heat release capacity HRC of Poly(PT-fa) is 21.3J / g·K, and the total heat release THR is 2.9kJ / g. The test results show that the HRC and THR of Poly(PT-fa) are lower than the HRC and THR values of the curing resin of all-bio-based benzoxazine synthesized by the existing solvent-free method, which indicates that Poly(PT-fa) has excellent flame retardant properties.
[0084] Since bisphenol A-aniline benzoxazine resin is a commercial resin, and its raw material bisphenol A-aniline benzoxazine is also prepared by a solvent-free method and is commercially available, in order to prove that Poly(PT-fa) has good thermal stability and flame retardant properties, Comparative Example 1 is provided, which is a method for preparing bisphenol A-aniline benzoxazine resin.
[0085] Comparative Example 1
[0086] A method for preparing a bisphenol A-aniline benzoxazine resin, wherein the steps not specifically described are the same as those in Example 1, except that: step 1 is not required, and in step 2, bisphenol A-aniline benzoxazine BA-a is used instead of PT-fa to obtain a bisphenol A-aniline benzoxazine resin, referred to as Poly(BA-a).
[0087] The TGA test results of Poly(BA-a) are as follows Fig.10 As shown, the T of Poly(BA-a) di The residual carbon rate Y at 328℃ and 800℃c Compared with Example 1, the T di Similar to Poly(PT-fa), however, the Y c Y relative to Poly(BA-a) c The results showed that the thermal stability of Poly(PT-fa) was significantly improved compared with that of Poly(BA-a).
[0088] The MCC test results of Poly(BA-a) are as follows Fig.11 As shown in the figure, the heat release capacity HRC of Poly(BA-a) is 166.2J / g·K, and the total heat release THR is 21.5kJ / g. Compared with Example 1, the HRC of Poly(PT-fa) is only 12.8% of the HRC of Poly(BA-a), and the THR of Poly(PT-fa) is only 13.5% of the THR of Poly(BA-a). The test results show that the flame retardant performance of Poly(PT-fa) is significantly improved compared with Poly(BA-a).
[0089] By comparing Example 1 and Comparative Example 1, it can be seen that the resin, Poly(PT-fa), which is also prepared based on the solvent-free method, has significantly improved thermal stability and flame retardancy compared to commercial Poly(BA-a).
[0090] In order to demonstrate the effect of the reaction medium on the preparation of PT-fa, that is, the difference between the solvent-free method and the solvent method, Comparative Example 2 is provided, which is a method for preparing a flame retardant bio-based benzoxazine resin based on a solvent method.
[0091] Comparative Example 2
[0092] A method for preparing a flame retardant bio-based benzoxazine resin based on a solvent method, wherein the steps not specifically described are the same as those in Example 1, except that: in the step 1, 100 mL of ethanol is added as a solvent, and since the boiling point of ethanol is 78° C., the reaction temperature is adjusted to 78° C., thereby obtaining a flame retardant bio-based benzoxazine resin based on a solvent method, referred to as PT-fa-EA.
[0093] To demonstrate the successful synthesis of PT-fa-EA, 1 H NMR test. The test results are as follows Fig.12 As shown, PT-fa-EA contains characteristic hydrogen spectra of furan ring, benzene ring, methylene on oxazine ring, methylene and ethylene connecting furan ring, and no other obvious impurity peaks. Compared with Example 1, it can be seen that there is no obvious difference between PT-fa-EA and PT-fa, that is, PT-fa can be prepared based on solvent method.
[0094] In order to demonstrate the effect of the solvent method on the yield of PT-fa, the mass of the obtained PT-fa-EA was weighed and calculated. The yield of PT-fa-EA was 60.8%. Compared with Example 1, it can be seen that the yield of PT-fa-EA synthesized by the solvent method is significantly lower than that of the solvent-free method.
[0095] By comparing Comparative Example 2 with Example 1, it can be seen that although PT-fa can be successfully prepared based on the solvent method, the yield of PT-fa-EA is much lower than that of the solvent-free method and cannot meet the application requirements.
[0096] In order to demonstrate the effects of reaction conditions, namely reaction temperature and reaction time, on the preparation of PT-fa, Comparative Example 3 is provided.
[0097] Comparative Example 3
[0098] A method for preparing a flame retardant bio-based benzoxazine resin, wherein the steps not specifically described are the same as those of Example 1, except that: in the step 1, the reaction is carried out at a reaction temperature of 100° C. and a reaction time of 2 h, and the material obtained in the step 1 is referred to as PT-fa-2.
[0099] To demonstrate the successful synthesis of PT-fa-2, 1 H NMR test. The test results are as follows Fig.13 As shown, PT-fa-EA contains the characteristic hydrogen spectrum of furan ring, benzene ring, methylene on oxazine ring, methylene and ethylene connecting furan ring, and no other obvious impurity peaks. Compared with Example 1, it can be seen that PT-fa-2 has no obvious difference with PT-fa, that is, PT-fa can be prepared based on different reaction conditions.
[0100] In order to demonstrate the effect of reaction temperature and reaction time on the yield of PT-fa, the mass of the obtained PT-fa-2 was weighed and calculated. The yield of PT-fa-2 was 67.3%. Compared with Example 1, the results show that lowering the reaction temperature and shortening the reaction time will reduce the yield of PT-fa.
[0101] By comparing Comparative Example 3 with Example 1, it can be seen that although PT-fa can be successfully synthesized by lowering the reaction temperature and shortening the reaction time, its yield is significantly reduced and cannot meet the requirements of high-yield synthesis.
[0102] In order to demonstrate the effect of the curing process on the preparation of Poly(PT-fa), Comparative Example 4 is provided.
[0103] Comparative Example 4
[0104] A method for preparing a flame retardant bio-based benzoxazine resin, wherein the steps not specifically stated are the same as those of Example 1, except that in step 2, the curing is divided into three stages, namely, only stages 1, 2 and 3 are performed, and stage 4 is not performed. The obtained material is referred to as Poly(PT-fa)-2.
[0105] In order to prove that Poly(PT-fa) can be prepared under different curing processes, TGA test was carried out. The test results are as follows Fig.14 As shown, the temperature T at which Poly(PT-fa) loses 5% of its weight under nitrogen atmosphere di The carbon residue rate Y at 321℃ and 800℃ c The test results show that the curing process of Poly(PT-fa) will affect the thermal stability of the resin.
Claims
1. A flame retardant bio-based benzoxazine resin Poly (PT-fa), characterized in that: The cured resin Poly(PT-fa) was prepared by thermal curing of the bio-based benzoxazine monomer PT-fa, and the obtained resin had high thermal stability and high flame retardancy. The PT-fa is prepared by using hydroxytyrosol, furfurylamine and paraformaldehyde as raw materials through a solvent-free synthesis method, and the obtained monomer has high purity.
2. The flame retardant bio-based benzoxazine resin Poly (PT-fa) according to claim 1, characterized in that: The synthesis yield of the monomer PT-fa is 80-90%.
3. The flame retardant bio-based benzoxazine resin Poly (PT-fa) according to claim 1, characterized in that: The temperature T at which the Poly(PT-fa) loses 5% of its weight under nitrogen atmosphere di The residual carbon rate Y at 310-330℃ and 800℃ c It is 60-70%.
4. The flame retardant bio-based benzoxazine resin Poly (PT-fa) according to claim 1, characterized in that: The heat release capacity HRC of the Poly (PT-fa) is 15-25 J / g·K, and the total heat release THR is 2-4 kJ / g.
5. A method for preparing a flame retardant bio-based benzoxazine resin Poly (PT-fa), characterized in that The following steps are involved: Step 1, preparation of bio-based benzoxazine monomer PT-fa, hydroxytyrosol, furfural amine and paraformaldehyde satisfying a certain amount of substance ratio, hydroxytyrosol, furfural amine and paraformaldehyde are mixed, and a Mannich condensation reaction is carried out under certain conditions by a solvent-free method. After the reaction is completed, the bio-based benzoxazine monomer is obtained after recrystallization and drying, which is referred to as PT-fa; Step 2, curing of the heat-resistant bio-based benzoxazine resin, first, under certain conditions, the PT-fa obtained in step 1 is completely melted, then the molten PT-fa is placed in a mold, and finally, the PT-fa is cured to obtain a heat-resistant bio-based benzoxazine resin, referred to as Poly(PT-fa).
6. The preparation method according to claim 5, characterized in that: In the step 1, the molar ratio of hydroxytyrosol, furfurylamine and paraformaldehyde is 1:2:
4.
7. The preparation method according to claim 5, characterized in that: In the step 1, the conditions for the Mannich condensation reaction are: in an oil bath and under stirring conditions, the reaction temperature is 110° C. and the reaction time is 6 h; In the step 1, the recrystallization operation is carried out in ethanol.
8. The preparation method according to claim 5, characterized in that: In the step 2, the conditions for complete melting of PT-fa are: a heating temperature of 115-140° C. and a heating time of 5-30 min.
9. The preparation method according to claim 5, characterized in that: In step 2, the curing conditions are divided into 4 stages: Stage 1: curing temperature is 180°C and curing time is 1h; Stage 2: curing temperature is 200°C and curing time is 1h; Stage 3: curing temperature is 220°C and curing time is 1h; Stage 4 is a curing temperature of 240°C and a curing time of 2 hours.